Iterating the Sum of Möbius Divisor Function and Euler Totient Function - Daeyeoul Kim; Umit Sarp; Sebahattin Ikikardes (Mathematics, 2019)
In this paper, according to some numerical computational evidence, we investigate and prove certain identities and properties on the absolute Möbius divisor functions and Euler totient function when they are iterated. Subsequently, the relationship between the absolute Möbius divisor function with Fermat primes has been researched and some results have been obtained.